Impact of Radiation Therapy Techniques on Hippocampal Doses and Psychological Status in Patients With Nasopharyngeal Carcinoma - Gai X; Huang S; Zeng J; Chen J; Liu F; Li S; Lv W; Guo F; Cai C; Hong J; Su L (Cancer Management and Research)
Xiujuan Gai,1– 3,* Shiqi Huang,1,2,* Jiang Zeng,1,2,4 Jun Chen,1,2,4 Feng Liu,1,2,4 Shan Li,1,2,4 Wenlong Lv,1,2,4 Feibao Guo,1,2,4 Chuanshu Cai,1,2,4 Jinsheng Hong,1,2,4 Li Su1,2,4 1Department of Radiotherapy, Cancer Center, The First Affiliated Hospital of Fujian Medical University, Fuzhou, 350005, People’s Republic of China; 2Department of Radiotherapy, National Regional Medical Center, Binhai Campus of the First Affiliated Hospital, Fujian Medical Universisty, Fuzhou, Fujian, 350212, People’s Republic of China; 3Department of Oncology, Laiyang Central Hospital of Yantai, Yantai, 265200, People’s Republic of China; 4Key Laboratory of Radiation Biology of Fujian Higher Education Institutions, The First Affiliated Hospital, Fujian Medical University, Fuzhou, 350005, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li Su; Jinsheng Hong, Department of Radiotherapy, Cancer Center, The First Affiliated Hospital of Fujian Medical University, Fuzhou, 350005, People’s Republic of China, Email lily2230@126.com; 13799375732@163.comPurpose: To investigate the impact of Intensity-Modulated Radiation Therapy (IMRT) and Volumetric Modulated Arc Therapy (VMAT) on hippocampal radiation dosage and psychological status in patients newly diagnosed with nasopharyngeal carcinoma (NPC).Patients and Methods: A retrospective analysis was conducted on 269 NPC patients who received initial treatment between January 2013 and April 2022. Patients were categorized into the IMRT group and the VMAT group based on the radiotherapy technique employed. The differences in hippocampal doses for NPC patients at different stages between the two groups were analyzed. The Hospital Anxiety and Depression Scale (HADS) was used to assess patients’ anxiety and depression states. Before radiotherapy, patients with anxiety scores (HADS-A) between 0 and 10 points were included to analyze the differences in anxiety occurrence rates between IMRT and VMAT techniques. Similarly, patients with depression scores (HADS-D) between 0 and 10 points were included to analyze the differences in depression occurrence rates between the two radiotherapy techniques.Results: In patients with T1-2 stage, those treated with IMRT had significantly higher hippocampal doses compared to those treated with VMAT. Furthermore, after radiotherapy, the occurrence rates of anxiety (HADS-A ≥ 11) and depression (HADS-D ≥ 11) in the IMRT group were 27.3% and 19.5%, respectively, while in the VMAT group, they were 9.5% and 7.4%, both showing significant statistical differences (P=0.010, P=0.035). However, there was no significant correlation between the radiotherapy technique and anxiety or depression occurrence rates in patients with T3-4 stage. Additionally, age and gender exhibited certain influences on psychological status.Conclusion: In the absence of hippocampal protection, opting for a VMAT treatment plan over IMRT may potentially reduce the incidence of anxiety and depression. This perspective offers new insights for optimizing treatment strategies and improving quality of life.Keywords: nasopharyngeal carcinoma, IMRT, VMAT, hippocampal doses, psychological status